ANALISIS PERTIMBANGAN PETANI DAN EFEKTIVITAS PRODUKSI IKAN NILA PADA KOLAM AIR TENANG DAN KOLAM AIR DERAS DI DESA SUKA NEGERI KECAMATAN AIR NIPIS KABUPATEN BENGKULU SELATAN - Agusmin, Wengki Abta; Fariadi, Herri; Nurmalia, Ana (University of Prof. Dr. Hazairin, SH, 2025)
Suka Negeri Village, Air Nipis District, South Bengkulu Regency is a village located in Bengkulu Province. Most of the residents of Suka Negeri Village depend on agriculture for their livelihood, namely rice, rubber, and palm oil farmers. In addition, the population is also engaged in fisheries, one of which is aquaculture. One of the fishery commodities that has bright prospects in this area is tilapia. Tilapia is a type of freshwater fish that has high economic value and is in demand by the community. The purpose of this study was to identify farmers' considerations and the effectiveness of tilapia production using still water ponds and fast-flowing water ponds in Suka Negeri Village, Air Nipis District, South Bengkulu Regency. The research method used was descriptive analysis using Likert scale measurements. The results of the study showed that tilapia farmers in Suka Negeri Village considered using still water ponds because the maintenance costs were cheaper with a percentage of cheaper maintenance costs of 51.8%. Meanwhile, tilapia farmers in Suka Negeri Village used fast-flowing water ponds because their production was higher, with a higher production percentage of 52.6%. For the effectiveness of tilapia production in still water ponds in Suka Negeri Village, Air Nipis District, it had a percentage of 53.91%, this value was included in the less effective category. Meanwhile, the effectiveness of tilapia production in fast-flowing water ponds in Suka Negeri Village, Air Nipis District, had a percentage of 70.58%.